Bio-Mediated synthesis and characterisation of Silver Nanocarrier, and its potent anticancer action - Lee, Kar Xin; Shameli, Kamyar; Shaza Eva M,; Yew, Yen Pin; Eleen Dayana, M. I.; Yap, Hooi Yeen *; Lim, Wei Ling *; Teow, Sin Yeang * (MDPI, 2019)
Discovery of a potent drug nanocarrier is crucial for cancer therapy in which drugs often face challenges in penetrating efficiently into solid tumours. Here, biosynthesis of silver nanoparticles (AgNPs) using a waste material, Garcinia mangostana (GM) fruit peel extract is demonstrated. The best condition for AgNPs synthesis was with 0.5 g of peel extract, 7.5 mM silver nitrate at 45 ◦C, ~pH 4 for 16 h. The synthesized AgNPs were spherical and 32.7 ± 5.7 nm in size. To test its efficiency to be used as drug carrier, plant-based drug, protocatechuic acid (PCA) was used as a test drug. AgNPs loaded with PCA (AgPCA) resulted in 80% of inhibition at 15.6 µg/mL as compared to AgNPs which only killed 5% of HCT116 colorectal cells at same concentration. The IC50 of AgNPs and AgPCA for HCT116 were 40.2 and 10.7 µg/mL, respectively. At 15.6 µg/mL, AgPCA was not toxic to the tested colon normal cells, CCD112. Ag-based drug carrier could also potentially reduce the toxicity of loaded drug as the IC50 of PCA alone (148.1 µg/mL) was higher than IC50 of AgPCA (10.7 µg/mL) against HCT116. Further, 24-h treatment of 15.6 µg/mL AgPCA resulted in loss of membrane potential in the mitochondria of HCT116 cells and increased level of reaction oxygen species (ROS). These could be the cellular killing mechanisms of AgPCA. Collectively, our findings show the synergistic anticancer activity of AgNPs and PCA, and its potential to be used as a potent anticancer drug nanocarrier.